Effective Communication About Pregnancy, Birth, Lactation, Breastfeeding and Newborn Care: The Importance of Sexed Language - Gribble, Karleen D.; Bewley, Susan; Bartick, Melissa C.; Mathisen, Roger; Walker, Shawn; Gamble, Jenny; Bergman, Nils J.; Gupta, Arun; Hocking, Jennifer J.; Dahlen, Hannah G. (Frontiers in Global Women's Health, 2022)
Maternal deaths from non-medical causes such as suicide and injury, are gaining increased attention from leading health bodies such as the World Health Organization, with calls to extend reporting to a year after birth (21). Even in the wealthiest contexts, early discontinuation of breastfeeding is responsible for a large proportion of infant hospitalisations (24). [...]Article 25 of the Universal Declaration of Human Rights says that the states of “motherhood and childhood are entitled to special care and assistance” (25) and the United Nations Convention on the Rights of the Child states that the best interests of the child are paramount (26). In this context, supporting autonomy is a legitimate and ethical goal, but the principles of distributive justice, to respect the equality, and dignity of every individual in the population must also be considered (47). The term “girls” may be avoided altogether with minors not disaggregated from adult women who are pregnant or mothers.